Detection of Genes Determining the Quality Characteristics of Maize Grain and its Resistance to Stress Factors - Markovskyi, OV, O.V.; Bannikova, M.O.; Borisova, V.V.; Fedorenko, T.V.; Morgun, B.V. (Science and Innovation, 2024)
Two hundred experimental samples of maize (Maize Company) have been examined for the presence of genes determining the quality characteristics of grain (wx and fl-2 genes) and resistance to herbicide (bar (pat), epsps genes) and pests (cry-genes). The maize DNA has been extracted from living vegetable tissue. The primers to detect the wx, fl-2, bar (pat), mepsps, CP4 epsps, cry1A(b), cry1F, cry1A.105, mcry3A, cry2Ab2, cry3Bb1, cry34Ab1, and cry35Ab1 genes have been selected and designed. The multiplex and the touchdown polymerase chain reaction (PCR) techniques have been developed. The PCR amplification of certain sequences has been carried out. None of transgenes (bar (pat), mepsps, CP4 epsps, cry1A(b), cry1F, cry1A.105, mcry3A, cry2Ab2, cry3Bb1, cry34Ab1, and cry35Ab1) has been found among the 200 analyzed maize experimental samples. At the same time, the fl-2 gene has been detected in 41 samples, whereas the wx gene has been identified in 192 analyzed samples.